2013
DOI: 10.2478/raon-2013-0059
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemotherapy as a new therapeutic strategy in advanced Merkel cell carcinoma of head and neck region

Abstract: BackgroundMerkel Cell Carcinoma (MCC) is a rare and aggressive tumour, arising from a cutaneous mechanoceptor cell located in the basal layer of epidermis, with poor prognosis. The treatment of choice for the initial stage of the disease is surgery and/or radiotherapy. The treatment of recurrent or advanced disease is still controversial.Case reportWe report a case of 84 years old woman with a recurrent MCC of the chin treated with electrochemotherapy (ECT). During the period of 20 months, four sessions of ECT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Efficacy of electrochemotherapy has been reported to be independent of the treated tumour types [14,15,42,49,82,92]. Similarly, in the current review, electrochemotherapy was found to be effective for basal cell carcinoma [2,21,50,78,93], malignant melanoma [2,5,12,13,17,21,23,36,40,73,74,79,92,[94][95][96][97], cutaneous lesions of breast cancer [2,63,64,80], squamous cell carcinoma [2,21,96,[98][99][100], Kaposi's sarcoma [55][56][57], Merkel cell carcinoma [41,60,61,96,101], and other tumours. The efficacy of this method is presented in more detail in table 2.…”
Section: Clinical Responses To Electrochemotherapy For Malignant Cutasupporting
confidence: 60%
See 1 more Smart Citation
“…Efficacy of electrochemotherapy has been reported to be independent of the treated tumour types [14,15,42,49,82,92]. Similarly, in the current review, electrochemotherapy was found to be effective for basal cell carcinoma [2,21,50,78,93], malignant melanoma [2,5,12,13,17,21,23,36,40,73,74,79,92,[94][95][96][97], cutaneous lesions of breast cancer [2,63,64,80], squamous cell carcinoma [2,21,96,[98][99][100], Kaposi's sarcoma [55][56][57], Merkel cell carcinoma [41,60,61,96,101], and other tumours. The efficacy of this method is presented in more detail in table 2.…”
Section: Clinical Responses To Electrochemotherapy For Malignant Cutasupporting
confidence: 60%
“…It can therefore be used at lower doses than those needed for classic chemotherapies [7,13,31]. In previous studies, electrochemotherapy with bleomycin was found to be effective for primary and metastatic malignant melanoma [2,5,17,20,30,[36][37][38][39][40][41][42][43][44][45][46][47][48][49], primary and metastatic basal cell carcinoma [2,21,38,44,[50][51][52], primary and metastatic squamous cell carcinoma [44,47,49,53], Kaposi's sarcoma [41,43,49,[54][55][56][57][58][59], Merkel cell carcinoma [41,60,61], cutaneous primary and metastatic lesions of breast cancer [49,[62][63]…”
Section: Choice Of Chemotherapeutic Agent For Electroporationmentioning
confidence: 99%
“…Electrochemotherapy is a relatively new treatment modality which can find indication in locally advanced lesions [34].…”
Section: Treatment Of Extra-nodal Locoregional Disease: Surgery/radiamentioning
confidence: 99%
“…Positive treatment results with BCC [11,118,122,[192][193][194][195][196][197][198][199][200] and SCC [122,172,187,[201][202][203] have been reported in several case series ( Table 7 ), while clinical experience in Merkel cell carcinoma [204][205][206] , sebaceous carcinoma [207] , and keratoacanthoma is still patchy [11,92,118,122,123,127,177,196,197,208,209] . ECT can be advantageous in patients with multifocal BCC (eg, in Gorlin-Goltz syndrome or Xeroderma Pigmentosum) to reduce the morbidity associated with repetitive surgical excisions [109,197] , and several creditable reports are available [109,47,192,193,199,210] .…”
Section: Nonmelanoma Skin Cancermentioning
confidence: 99%